Genotypic variability of Tunisian maize landraces: A valuable genetic resource to mitigate drought and heat stress in the Mediterranean basin - Mohamed Dhia Eddine Hammami; Zayneb Kthiri; Walid Hamada; Rosa Ana Malvar; Chahine Karmous; Pedro Revilla (PLoS ONE, 2025)
This study aimed to assess the drought and heat stress tolerance of nine Tunisian maize populations and their potential stress tolerance mechanisms. Over two years, nine Tunisian maize populations were evaluated under five environments with varying stress levels and one optimal growth condition in Tunisia. This work formed part of a larger study that includes a total of 223 Mediterranean maize landraces. The nine Tunisian populations were specifically chosen to assess the behavior of landraces adapted to the drought and heat stress conditions prevalent in the southern Mediterranean. In all the locations, the trials followed an augmented design with five blocks and a total of five checks over the two-year study period replicated in each block.The study demonstrated that combined drought and heat stress severely reduced maize yield, with Tunisian landraces experiencing losses of 76% to 95% relative to optimal conditions. Factorial regression analyses were performed to provide a biological interpretation of the contribution of environmental and genotypic variables, as well as their interactions, to grain yield variability. The most representative genotypic covariates were plant height (PH) followed by the number of ears (NE), thousand-grain weight (1000GW), and aerial biomass, respectively, explaining 26%, 12%, 9%, and 8% of the total variability. The significant environmental covariates were cumulative hydric deficit (DHC) and the average anthesis silking interval (ASI_ENV) in each environment, representing 48% of the total environmental variation. The interaction between thousand-grain weight and cumulative hydric deficit had the highest contribution (9%) of interaction for grain yield. The factorial regression indicated that under stress conditions, maize plants appeared to adapt to maintain yield by increasing thousand-grain weight while reducing aerial biomass, number of ears, and grain number. This response likely reflects an enhanced capacity for efficient resource reallocation, supporting the plant’s resilience under combined drought and heat stress conditions. The landraces BK, KAR, and MT2 consistently outperformed in most traits under stress conditions, showing significant tolerance and adaptability for across multiple stress levels with better yields and flowering synchronization. The selected best-performing populations could serve as valuable sources of drought and heat stress tolerance sources for future breeding programs.